MOTIVATIONAL CLIMATE AND ENJOYMENT IN PHYSICAL ACTIVITY IN ITALIAN HIGH-SCHOOL STUDENTS: DIFFERENCES BY GENDER (Fiep Bulletin - online, 2014)
The aim of the study is to examine the differences in high school adolescents in motivational climate and enjoyment according to gender and if motivational climate infl uences enjoyment in physical activity.207 high school  adolescents (males: n=118, age: 16±0.7 yrs,  h:172.3±5.4 cm, weight: 67.4±11.9 kg; females: n=89, age: 15.9±0.8 yrs, h: 159.5±5.9 cm, weight:59.2±10.2 kg) were asked to complete enjoyment and motivational climate self-reported questionnaires during physical education lessons. Anova one-way was performed to examine the effect of gender on motivational climate and on enjoyment. A multiple regression analisys was also performed to examine if there were any gender differences in the prediction of enjoyment in physical activity.Data were analyzed by sPss ver.13 and signifi cance was set at p
Keywords: motivational climate; enjoyment; young; gender